Screening for distress, the sixth vital sign, in lung cancer patients: effects on pain, fatigue, and common problems—secondary outcomes of a randomized controlled trial. Issue 8 (12th November 2012) - Carlson, Linda E.; Waller, Amy; Groff, Shannon L.; Bultz, Barry D.
Abstract: Background: This randomized controlled trial examined the impact of an online routine screening for distress program on physical symptoms and common psychosocial and practical problems in lung cancer outpatients. Method: Patients were randomly assigned to either the minimal screening group (the Distress Thermometer plus usual care); full screening group (Distress Thermometer, Canadian Problem Checklist (CPC), Pain Thermometer, Fatigue Thermometer, and the Psychological Screen for Cancer Part C, with a personalized report summarizing concerns); or triage (full screening plus option of personalized phone triage). Outcomes included pain, fatigue and psychosocial, practical and physical problems. Patients were reassessed 3 months later. Results: A total of 549 lung patients completed baseline measures (89% of eligible patients) and 65.9% were retained at 3 months. At 3 months follow‐up, significantly fewer patients in the triage group (32.1%) reported pain compared with the minimal screening group (49.6%), but the triage and full screening groups were not significantly different from one another. Patients in the triage group reported fewer problems with coping compared with the minimal and full screening groups and fewer problems with family conflict compared with the minimal screening group. Full screening patients reported fewer problems with breathlessness compared with the minimal screening group. No differences were found among groups in fatigue. Referrals were not associated with changes in outcomes over time. Conclusions: Routine screening for distress followed by personalized triage resulted in the most benefit for lung patients, with fewer fully screened and triaged patients reporting physical symptoms and psychosocial problems than those only minimally screened. Copyright © 2012 John Wiley & Sons, Ltd.